(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Heterocyclic compounds are widely recognized for their therapeutic importance in the treatment of numerous diseases. Network pharmacology has emerged as a powerful approach for exploring the molecular mechanisms and therapeutic potential of bioactive compounds. In the present study, a series of chalcone-derived quinoxaline derivatives were designed and examined for their potential using integrated network pharmacology and computational studies. According to network pharmacology and enrichment analyses, the designed derivatives were found to be exerts their potential against breast cancer by targeting the ESR1, AKT1 and PIK3CA targets. The physicochemical properties, pharmacokinetic behaviour and toxicity profiles of the designed compounds were assessed, indicating druggable nature. Drug score values ranged from 0.28 to 0.51, calculated using the OSIRIS Molecular Property Explorer, and highlights their viability for further clinical development. Molecular docking studies performed using the PyRx against the selected targets showed that compounds 4b and 4e were found to be potent, with binding energies of -9.6 Kcal/Mol (4e), −9.7 Kcal/Mol (4b) and -14.8 Kcal/Mol (4e) against ESR1, AKT1 and PIK3CA respectively. Furthermore, density functional theory (DFT)-based graph theoretical analysis confirmed the structural stability and correlated with the biological potential of the compounds. Overall, these findings suggest that the designed chalcone-quinoxaline derivatives may be used as therapeutic candidates for the management of breast cancer. However, in vitro and in vivo studies are warranted.